L'investitura notarile e la validità degli instrumenta alle soglie del Duecento. Il caso del notaio Domenico da Pirano - Zabbia, Marino (Scrineum, 2013)
This essay deals with the notarial investiture in Istria in the Thirteenth Century. The study starts with the notarial records written at the beginning of the Century by the notary Domenico di Pirano, whose validity was denied during the trial. Who had doubts about the validity of the documents claimed that Domenico was not appointed by someone who had the authority to do it. On the contrary, who considered the documents valid, affirmed that Domenico in Pirano was commonly considered a notary that was invested with power during a public ceremony. Besides, there was a reference to Roman and Canon law, that allows to affirm that the documents written by someone who is commonly regarded as notary are to be considered valid also in case of discovery of an illegitimate appointment. In the essay the Domenico case is compared both to a similar but less proved event, occurred in Istria at the beginning of the Thirteenth Century too, and to information regarding notary investitures in this same region available for Thirteen Century and the first half of the Fourteenth Century, underlying the role held by the Istrian marquises on the notary appointments.